Undergraduate Electrical Engineering Student’s Perspectives on Lecturers’ Teaching Methodologies at President University as EMI University - Ida Bagus Putu Arkananta; Fiqih Nuraffi Rachmansyah; Ghania Rabbanni Hidayat; Nabila Nur Halisa; Gigih Angun Farmala (Publikasi Indonesia, 2026)
English-Medium Instruction (EMI) has become increasingly important in higher education, particularly in engineering programs where English is widely used as the medium of instruction. This study aimed to investigate undergraduate Electrical Engineering students’ perceptions of lecturers’ teaching methodologies in EMI classrooms, particularly in the Control Systems course at President University. A quantitative descriptive survey design was employed, involving 21 undergraduate students. Data were collected using a 20-item questionnaire measured on a 6-point Likert scale. Instrument reliability testing demonstrated excellent internal consistency (Cronbach’s alpha = 0.979). Data were analyzed using descriptive statistics, including frequencies, percentages, mean scores, and standard deviations. The findings revealed generally positive student perceptions of EMI teaching methodologies, with all questionnaire items obtaining mean scores above 4.00. Students reported that clear explanations, opportunities for interaction, and the use of supportive learning media enhanced their understanding and engagement in the learning process. Nevertheless, several students continued to experience challenges related to English language proficiency and technical terminology. These findings suggest that adaptive and student-centered teaching methodologies play an important role in maximizing learning effectiveness within EMI engineering classrooms.